Animal law protection in Colombia: Legal, political, economic perspectives and in the territory (2021)
This work aims to present a comprehensive overview of the state of the legal-political protection of animals in Colombia. The Colombian State is going through a period of institutional and socio-legal transformation. The once widespread model of the relationship between the legal system and animals as things or simple elements of the environment is being re-evaluated and a whole number of problems arise which must be addressed from new approaches and perspectives. This book focuses on topics such as crimes and misdemeanors, the use of animals for human consumption, animal used on research and testing, the use of animals for security purposes, the development of public policies and their interrelation with the movement of the civil society first from an analytical plane and then contextualized in different cities of Colombia.